COMOVEMENT ANALYSIS OF GLOBAL CRUDE OIL PRICE PRICE AGAINST STOCK PRICE OF CERTAIN OIL AND GAS COMPANIES USING WAVELET COHERENCE - Zakiy Muyamman, Ahmad
Econophysics is a discipline in physics with economics as the main object of discussion. Various phenomena that occur in economics are studied and examined using existing laws and rules in physics. One of the problems that Econophysics is discussing is the ups and downs of world oil prices and their impacts. Petroleum is one of the most widely used energy sources today because petroleum sources are still available in large quantities. Shares are proof of individual ownership of a company. If someone or a group has a portion of shares of a company, it means that the person already owns a portion of the company so that person has the right to have the profit owned by the company. Comovement is a movement together or in the same direction between two or more prices of financial instruments, commodities or exchange rates. If there is an event that causes the price of a stock to move down simultaneously with other shares also going down then it can be called having a high comovement. Wavelet function is one method for analysing time and frequency domains at once. Oil prices and stock prices which are time series are transformed into wavelet functions that have both time and frequency domains at once. From this information it can be seen that the volatility of the time series and also the comovement between two different time series.